INOVASI SOSIAL MELALUI PROGRAM CSR PT PLN (PERSERO) UNIT INDUK TANJUNG JATI B - Arifin, Miftah; Khoriul Anam, A.; Mahaputra, Wahyu (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2021)
Empowerment is one of the strategies used in community development at this time. it can increase knowledge and power to reach a state of empowerment. one of the funding source empowerment programs comes from the Corporate Social Responsibility (CSR). PT. PLN (Persero) Tanjung Jati B Generation Main Unit sees that there are vulnerable groups that have the potential to be developed in their business management, these groups are the disabled community "Sadifa" Jepara. The approach used is by using a 4-pillar model, namely the community as a supporting system and community activities, MSME Center, a forum for communication and cooperation, and the development of environmentally friendly products. This empowerment program aims to strengthen the economy of the disabled community through various activities such as making herbal drinks, various types of soap, hand sanitizer, convection business, basic food business, and so on. In addition, the activities carried out include various types of training to strengthen MSMEs, providing equipment assistance, opportunities to develop networks by means of mass media publications as well as initiatives for sustainable and environmentally friendly economic activities.